Treatment with a human recombinant monoclonal IgG antibody against oxidized LDL in atherosclerosis-prone pigs reduces cathepsin S in coronary lesions. (15th July 2016) - Poulsen, Christian Bo; Al-Mashhadi, Ahmed Ludvigsen; von Wachenfeldt, Karin; Bentzon, Jacob Fog; Nielsen, Lars Bo; Al-Mashhadi, Rozh H.; Thygesen, Jesper; Tolbod, Lars; Larsen, Jens Rolighed; Frøkiær, Jørgen; Tawakol, Ahmed; Vucic, Esad; et al.
Abstract: Background: Immunization with oxidized LDL (oxLDL) reduces atherosclerosis in rodents. We tested the hypothesis that treatment with a human recombinant monoclonal antibody against oxLDL will reduce the burden or composition of atherosclerotic lesions in hypercholesterolemic minipigs. Methods and results: Thirty-eight hypercholesterolemic minipigs with defective LDL receptors were injected with an oxLDL antibody or placebo weekly for 12 weeks. An 18F-fluorodeoxyglucose positron emission tomography (FDG PET) scan (n = 9) was performed before inclusion and after 3 months of treatment. Blood samples were obtained prior to each injection. Following the last injection all animals were sacrificed, and the heart, aorta, and iliac arteries were removed. The left anterior descending coronary artery was sectioned at 5 mm intervals for quantitative and qualitative assessments of atherosclerosis, including immunohistochemical phenotyping of macrophages using a pan-macrophage marker (CD68) and markers for putative pro-atherogenic (cathepsin S) and atheroprotective (CD163) macrophages. Aorta, right coronary artery, and left iliac artery were stained en face with Sudan IV and the amount of atherosclerosis quantified. There was no effect of treatment on plasma lipid profile, vascular FDG-PET signal or the amount of atherosclerosis in any of the examined arteries. However, immunostaining of coronary lesions revealed reduced cathepsin S positivity in the treated group compared with placebo (4.8% versus 8.2% of intima area, p = 0.03) with no difference in CD68 or CD163 positivity. Conclusions: In hypercholesterolemic minipigs, treatment with a human recombinant monoclonal antibody against oxLDL reduced cathepsin S in coronary lesions without any effect on the burden of atherosclerosis or aortic FDG-PET signal.